EU Cohesion Policy Implementation - Evaluation Challenges and Opportunities The 1st International Conference on Evaluating Challenges in the Implementation of EU Cohesion Policy (EvEUCoP 2022), Coimbra, 2022 - Henriques, Carla; Viseu, Clara; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This open access book is the result of the 1st International Conference on Evaluating Challenges in the Implementation of EU Cohesion Policy (EvEUCoP 2022). It presents the recent findings, sparks discussion, and reveals new research paths addressing the use of novel methodologies and approaches to tackle the challenges and opportunities that are unveiled with the implementation of the EU cohesion policy. The authors cover a wide range of topics including the monitoring of data; the clearness of indicators in measuring the impact of interventions; novel evaluation methods, addressing the mid-term and terminal assessment; as well as case studies and applications on evaluations of the thematic objectives under the scrutiny of the cohesion policy, namely: Research, technological development, and innovation; Information and communication technologies; Shift toward a low-carbon economy. During the 2014-2020 programmatic period, member states were required to undertake assessments to evaluate the efficacy, efficiency, and impact of each operational program. Such evaluations are generally concerned with the compliance of projects and activities with programmatic priorities, as well as with funds' absorption capacity and refer to ex-ante and ex-post assessments. Hence, this book proposes the use of novel methodologies addressing the mid-term and terminal assessments that enable performing the efficiency appraisal of the operational programs and that can support decision-makers in the selection of projects that should be awarded for funding.
Part I. Mid-term/terminal assessment: Data Envelopment Analysis approaches -- Chapter 1. Evaluating the reasons behind the inefficient implementation of ERDF devoted to R&I in SMEs (Carla Henriques) -- Chapter 2. Are ERDF devoted to boosting ICT in SMEs inefficient? Insights through different DEA models (Carla Henriques) -- Chapter 3. Are ERDF devoted to boosting ICT in SMEs inefficient? Further insights through the joint use of DEA with SFA models (Carla Henriques) -- Chapter 4. Python implementation of the Value-Based DEA method (António Trigo) -- Chapter 5. Are ERDF efficient in strengthening the switch to a Low-Carbon Economy? Some Insights with Value-Based Data Envelopment Analysis (Maria Gouveia) -- Part II. Ex-post assessment: Meta-analysis -- Chapter 6. Firm competitiveness, specialization, and employment growth: territorial level Relationships (Federico Fantechi) -- Chapter 7. The youth guarantee in Eastern Europe. A systematic review(Gabriela Neagu) -- Part III. Methodologies for supporting the selection of projects -- Chapter 8. Smart and Sustainable Scheduling of Charging Events for Electric Buses (Padraigh Jarvis) -- Chapter 9. Multiple impacts of energy efficiency technologies in Portugal (Marcos Tenente) -- Part IV. Case studies -- Chapter 10. EU Operational Programmes Reporting: From Basics to Practices (Ana Amaro) -- Chapter 11. European structural and investment funds 2021-2027: prediction analysis based on machine learning models (Victor Santos) -- Chapter 12. Technology serving justice (Ana Paula Lopes).
Keywords: Political planning; Europe -- Politics and government; Economic development; Technological innovations; Economic policy; Environmental policy; Public Policy; European Politics; Economic Development, Innovation and Growth; Innovation and Technology Management; Economic Policy; Environmental Policy